A few key species drive community thermophilization under experimental warming - Kara C. Dobson; Kai Zhu; Yiluan Song; Jiali Zhu; Peter B. Adler; Michael Stemkovski; Rebecca Montgomery; Artur Stefanski; Kally Worm; Peter B. Reich (Proceedings of the National Academy of Sciences, 2026)
Community thermophilization—the process by which communities are increasingly dominated by species from warmer biogeographic regions—is a widespread ecological response to warming. However, most studies on thermophilization use observational data, making it difficult to directly attribute warming as the driver of thermophilization. Furthermore, knowledge of specific species that are key drivers of thermophilization may be especially relevant to natural resource management and restoration practices, but these key contributors are rarely identified in thermophilization studies. To address these gaps, we analyzed plant community data from six experimental warming studies across the United States. We quantified thermophilization within and across years using the Community Temperature Index (CTI), which reflects the average thermal affinity of species in a community, and then decomposed CTI changes into individual species contributions. Across experiments, warmed plots consistently had higher CTIs than ambient plots, demonstrating a clear causal effect of warming. In all experiments, thermophilization was driven by a small subset of species: The Gini coefficients for species contributions ranged from 0.49 to 0.85, indicating that a small number of species account for most of the contributions. These findings confirm warming as a driver for community thermophilization and highlight the key species responsible for the shifts in CTIs, which may be especially relevant for conservation initiatives aimed at increasing community resilience or maintaining ecosystem function in a warmer climate.